An Estimate of Abortion Incidence and Unintended Pregnancies - Ghimire, Jagadishwor; Lal, Bibek Kumar; Karki, Sujan; Mehata, Suresh; Dotel, Bhogendra Raj; Joshi, Nisha; Shrestha Pradhan, Gauri; Gautam, Manish; Shrestha Dangol, Deeb; Phuyal, Parash Prasad; Lamichhane, Kritee; Bhattarai, Navaraj; et al. (Journal of Nepal Health Research Council, 2024)
Background: After the legalization of abortion in Nepal, there has been remarkable changes in policies and service delivery. However, even after two decades of legalization, access to and use of safe abortion services remains limited. The objective of this study is to estimate the incidence of abortion and unintended pregnancies in Nepal.Methods: A cross sectional study was conducted in 767 health facilities using structured questionnaires to assess the availability of abortion services, and 231 key informant interviews were conducted. Information on medical abortion drugs was collected from distributors and pharmacies. Abortion estimations were segmented into categories: those performed within healthcare facilities, those conducted outside healthcare facilities, and those using other traditional methods. To estimate pregnancy outcomes, we utilized secondary data from national censuses and health surveys. Results: The total incidence of induced abortion cases in Nepal was estimated to be 333,343 for the year 2021. Only 48 percent of abortion services were provided from the listed (legal) sites and providers. The estimates showed that total facility based induced abortion in Nepal was 176,216 in 2021, more than half were medical abortions. The highest and lowest abortion cases were in Bagmati and Karnali province respectively. The result showed that more than half of the pregnancies were unintended (53.3%).Conclusions: Despite a relatively liberal legal environment, more than half of all abortions are extra-legal in Nepal. Unintended pregnancies are also common, resulting in induced abortion. This demands for increasing access to information and services on contraception and safe abortion among women and girls.Keywords: Abortion incidence; legal abortion; unintended pregnancy.